OP0101 Risk of opportunistic infections in patients with rheumatoid arthritis initiating abatacept: analysis of all available clinical trial data. (15th June 2017) - Simon, T; Gelarden, T; Nkhoma, E; Zhou, M; Banerjee, S; Winthrop, K
Abstract : Background: Opportunistic infections (OI) during treatment with abatacept (ABA) have been previously reported but are lacking a comprehensive analysis. Objectives: To present the overall incidence rates of OI and herpes infections observed in patients (pts) receiving ABA using combined clinical trial data. Methods: OI adverse events were summarized from 16 clinical trials (both placebo-controlled and cumulative abatacept exposure); all pts randomized to placebo were on a non-biologic DMARD. Incidence rates (per 100 person-years [p-y]) were calculated by the number of pts experiencing the first event divided by the total number of p-y of exposure. The p-y of exposure was censored at the time of the first event, death, discontinuation or end of study. Random effects meta-regression was performed across the trials to estimate the frequency of OI after adjusting for between-study heterogeneity. OI were identified using a pre-specified list in the setting of biologic therapy for patients with RA. Criteria for consideration were based on type, location of the infection and causing organism. Excluded from the list were non-specific infections caused by organisms considered to be opportunistic, but common in the general population. Results: A total of 7044 pts with RA with ∼21, 330 p-y of ABA exposure were included in the cumulative randomized trial data (Table). The frequency of OI was 64% lower among pts treated with ABA vs placebo. After adjusting for heterogeneity across studies, the frequency (95% CI) of OI remained lower for the ABA group (0.15% [0.06, 0.42] vs the placebo group (0.48% [0.22, 1.04]). Conclusions: Abatacept-treated pts had a lower incidence rate of OI compared with placebo. The OI and herpes infection incidence rates in the cumulative data are similar or lower to those reported in the literature. 1–3 References: Curtis JR, et al. Ann Rheum Dis 2016;75:1843–7. Yun H, et al. Arthritis Care Res (Hoboken) 2015;67:731–6. Winthrop KL, et al. Ann Rheum Dis 2015;74:2107–16. Disclosure of Interest: T. Simon Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, T. Gelarden Employee of: Alpha Consulting, E. Nkhoma Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Zhou Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Banerjee: None declared, K. Winthrop Consultant for: Pfizer, AbbVie, Bristol-Myers Squibb, UCB, Roche/Genentech, Amgen, Galapagos, Lilly